Exploring medical personnel’s discourses on the sexual health of lesbian and bisexual women in greater Lisbon, Portugal - Oliveira, João Manuel de (2014)
This qualitative exploratory study analysed the discourses of medical personnel on lesbian and bisexual women’s sexual health. We aimed at identifying the best practices to eradicate heteronormativity in this sector and enhance health care provision for this population. We interviewed 16 physicians in the metropolitan area of Lisbon using semi-structured interviews. The thematic analysis identified a lack of professional knowledge in dealing with non-heterosexual patients, despite the consensual discourse on the necessity of non-discriminatory practices.